THE EFFECT OF USE OF VIDEO MEDIA AND WORKSHOP ON THE LEARNING RESULTS OF CLASS VII STUDENTS MATHEMATICS SMP MUHAMMADIYAH 5 SILIRAGUNG - Mardiasari Dwi (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This research was conducted to instructional video media on the mathematics learning outcomes of Grade VII students of SMP Muhammadiyah 5 Siliragung. This research is quantitative research. With this type of causal quantitative research. The research was conducted in class VII, namely class VIIA and VIIC, for 62 students. Meanwhile, to test the validity and reliability of the Video questionnaire instrument (X1), Data collection techniques used questionnaires, mathematics learning outcomes tests and observation sheets. The data analysis technique used the multiple linear regression test to test the effect of video media and worksheets media on mathematics learning outcomes and simulant test (F test) to test the effect of using video media and worksheets together on mathematics learning outcomes. The results show that the regression coefficient of the learning video is 0.233, meaning that if the learning video variable (X1) increases by 1% assuming the LKS variable (X2) and the constant (a) is 0 (zero), then Student mathematics learning outcomes increased by 23.3% while the second regression test can be seen that the LKS media regression coefficient value is 0.325, meaning that if the LKS variable (X2) increases by 1% assuming the learning idea variable (X1) and the constant (a) is 0 (zero), then the students' mathematics learning outcomes increased by 32.5%. And based on the results of the simultaneous test (F test), it can be seen that if F count is 6.649 with F table value is 3.15 so that the Fcount value> F table or 6.649> 3.15, and a significant level of 0.000 <0.05, it can be concluded that independent variables have an influence on variables. dependent